Gait Disorders Questionnaire–Promising Tool for Virtual Reality Designing in Patients With Parkinson's Disease - Kosutzka, Zuzana; Kusnirova, Alice; Hajduk, Michal; Straka, Igor; Minar, Michal; Valkovic, Peter (Frontiers in Neurology, 2019)
Background Gait disorders (GD) are frequent and disabling symptoms in patients with Parkinson´s disease, mostly because they significantly limit mobility and often lead to fear of falls or actual falls. Nowadays rehabilitation is considered to be the most effective nonpharmacological approach to reduce risk of falls. Using paradigms in virtual reality (VR) is a promising tool in neurorehabilitation because of the potential improvement in motor learning and improvement in daily functioning by replicating everyday real-life scenarios. Objective To identify the most prevalent everyday situations which impair gait in PD that could be simulated in virtual reality (VR) environment. Methods A newly developed self-report questionnaire consisting of 15 binary response items (YES/NO) encompassing everyday walking situations was administered to 62 patients diagnosed with idiopathic PD according to MDS Clinical Diagnostic Criteria. We included patients able to walk unassisted for at least 10 minutes and without significant cognitive impairment. Mokken Scale Analysis was used to evaluate psychometric properties of the scale. Results Questionnaires from 58 patients were analysed (31 men, age=63±9.9y, disease duration= 7.02±4.03y, LEDD=1115±549.4mg, H&Y=2.4±0.6). Only 10 items (out of 15) were identified as scalable and these were included in Gait Disorders Questionnaire (GDQ). The most prevalent trigger of gait disorders was walking under time pressure, followed by gait in crowded places and walking while dual-tasking. The total score of GDQ significantly correlated with the disease duration (rs=0.347, p= 0.008) and modified H&Y staging (rs=0.288, p=0.028). Conclusion With the use of GDQ we identified the most prevalent everyday transition activities that provoke gait disorders in patients with PD. The results may be useful for further development and systematic application of VR paradigms for physiotherapy of PD patients.